Calculation of the thermal conductivity of human serum albumin (HSA) with equilibrium/non-equilibrium molecular dynamics approaches. (May 2020) - Ashkezari, Abbas Zarenezhad; Jolfaei, Nitasha Adavoodi; Jolfaei, Niyusha Adavoodi; Hekmatifar, Maboud; Toghraie, Davood; Sabetvand, Roozbeh; Rostami, Sara
Highlights: Investigation of thermal properties of human serum albumin structure with precise atomic arrangement. Using of equilibrium and non-equilibrium molecular dynamics approaches. HSA molecule is exactly represented by C, N, O and S atoms and implemented dreidng potential. EMD results are higher than NEMD results. Abstract: Background and objective: Human serum albumin (HSA) controls the flow of numerous chemical structures and molecules in the cardiovascular system. So, thermal conductivity of this atomic compound is important in medicinal applications. Methods: In this work, the thermal conductivity of HSA is calculated with equilibrium/non-equilibrium molecular dynamic approaches. In these methods each HSA molecule is exactly represented by C, N, O and S atoms and their implemented dreiding potential. Finally by using Green-Kubo and Fourier's law the thermal conductivity of HSA/H2 O mixture is calculated. Results: Our calculated rates for thermal conductivity via equilibrium/non-equilibrium molecular dynamics methods are 0.496 W/m K and 0.448 W/m K, respectively. The calculated thermal conductivity for this structure was very close to the thermal conductivity calculated for water molecules which were reported by other research groups. Furthermore our simulated structures show that thermal conductivity of HAS/H2 O mixtures has inverse relation with HAS molecules numbers and temperature of simulated atomic structures. Conclusions: Comparing thermal conductivity from equilibrium/non-equilibrium molecular dynamics methods for HAS/H2 O shows that EMD and NEMD results are reliable and EMD calculated results are higher than NEMD results.